A quintet of cuisines - Field, Michael 1915-1971 (Alexandria, Va. Time-Life Books, 1970)
Covers the cooking of five regions that include ten countries: Switzerland, the Low Countries (Belgium, Luxembourg, Netherlands), Poland, Bulgaria and Romania, North Africa (Tunisia, Algeria, Morocco).
Keywords: Cookery, International